Identification of novel signaling components in N,N’-Dinitrosopiperazine-mediated metastasis of nasopharyngeal Carcinoma by quantitative phosphoproteomics - Huang, Damao (BioMed Central, 2014)
BACKGROUND: Nasopharyngeal carcinoma (NPC) is a highly invasive and metastatic cancer. N,N’-dinitrosopiperazine (DNP), a carcinogen with specificity for nasopharyngeal epithelium, facilitates NPC metastasis. However, the underlying mechanism is not known. METHODS: Quantitative phosphoproteomics, using stable isotope labeling of amino acids in cell cultures, was employed to identify phosphoproteins associated with NPC metastasis mediated by DNP. NPC cell line 6-10B, which is relatively less metastatic, was used to investigate DNP-mediated metastasis. Boyden chamber invasion assay was used to measure DNP-induced motility and invasion, and nude mice were used to verify DNP-mediated metastasis in vivo. Several different phosphoproteins detected by proteomics analysis were verified by immunoblotting. DNP-mediated metastasis facilitated by lysine-rich CEACAM1 co-isolated protein (LYRIC) phosphorylation at serine 568 was confirmed using mutations targeting the phosphorylation site of LYRIC. DNP-mediated metastasis through LYRIC phosphorylation was confirmed in the NPC cell line CNE1. DNP-mediated LYRIC phosphorylation at serine 568 was also verified in metastatic tumors of BABL/c nude mice. RESULTS: Boyden chamber invasion assay indicated that DNP mediated cell motility and invasion of NPC cell 6-10B in vitro, and experiments with nude mice indicated that DNP increased 6-10B metastasis in vivo. In the phosphoproteomics analysis, we detected 216 phosphorylation sites on 130 proteins; among these, 48 phosphorylation sites on 30 unique phosphopeptides were modulated by DNP by at least 1.5-fold. DNP mediated the expression of phosphorylated GTPase, ferritin, LYRIC, and RNA polymerase, and it decreased the expression of phosphorylated torsin-1A protein 1. Furthermore, DNP induced LYRIC phosphorylation at serine 568 to facilitate cell motility and invasion, whereas DNP-mediated motility and invasion was decreased when serine 568 in LYRIC was mutated. In another NPC cell line, CNE1, DNP also mediated cell motility and invasion followed by enhanced phosphorylation of LYRIC at serine 568. Finally, phosphorylated-LYRIC expression at serine 568 was significantly increased in metastatic tumors induced by DNP. CONCLUSION: DNP regulates multiple signaling pathways through protein phosphorylation, including the phosphorylation of LYRIC at serine 568, and mediates NPC metastasis. These findings provide insights on the complexity and dynamics of DNP-facilitated metastasis, and may help to gain a better understanding of the mechanisms by clarifying NPC-induced metastasis.